The Analysis of Morphological and Genetic Characteristics of Yellowstripe Scad from Muara Baru Modern Fish Market in North Jakarta - Rahmat Sawalman; Hawis Madduppa (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightIdentification and morphological analysis of Selaroides leptolepis fish.Molecular analysis using the DNA Barcoding method with the COI gene (mitochondrial cytochrome oxidase subunit I).The number of base pairs in S. leptolepis from the sequencing results was 675bp.The morphological and molecular similarities of Selaroides leptolepis fishAbstractYellowstripe scad is one of the commercially important fish from the Carangidae family, which is marketed at Muara Baru Modern Fish Market, North Jakarta. In- formation regarding the presence of Selaroides leptolepis fish in the waters allows for effective conservation, and management of marine resources. A morphological identification of fish species is still considered inaccurate, so the molecular anal- ysis is necessary. This study aims to identify commercially important fish species deriving from Muara Baru Modern Fish Market, North Jakarta, employing mor- phological, and molecular analysis. A total of 30 specimens were collected from the field. The morphological analysis utilized a visual identification method, and morphometric measurement, while molecular analysis with DNA barcoding em- ployed the mitochondrial cytochrome oxidase subunit I (COI) gene. The results of the morphological analysis indicated that the fish species were yellowstripe scad (S. leptolepis). It also followed the results of molecular analysis of DNA barcoding that the fish was a S. leptolepis species. Therefore, the combination of morphological and genetic analysis has succeeded in identifying the fish species of S. leptolepis.